Analisis Literatur Sistematis tentang Faktor-Faktor yang Mempengaruhi Minat Berwirausaha pada Generasi Z : Pendidikan Kewirausahaan, Ekspektasi Pendapatan, dan Efikasi Diri - Rieke Nadyas Pitaloka; Putri Ulfa Kamalia (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to identify and synthesize the factors influencing entrepreneurial interest among Generation Z using a Systematic Literature Review (SLR) approach. The main focus of this review centers on three key variables: entrepreneurship education, income expectation, and self-efficacy. The background of this study is based on the high unemployment rate among Gen Z, particularly high school graduates, who have not yet shown a strong inclination toward entrepreneurship. A total of 89 articles were collected and screened, resulting in 13 selected articles that met the inclusion criteria and were deemed relevant. A thematic analysis was conducted to identify recurring patterns, similarities, and differences among the studies. The findings indicate that entrepreneurship education significantly influences entrepreneurial interest when implemented through practical, technology-based, and collaborative learning models. Income expectation also acts as a strong motivator, although its effect tends to be contextual and dependent on personal background and perception. Meanwhile, self-efficacy emerged as the most consistent and dominant factor, showing a strong and direct influence on entrepreneurial interest. It also serves as a mediating variable between entrepreneurship education and entrepreneurial intention. This review contributes theoretically by providing a structured synthesis of prior research and practically by offering recommendations to enhance entrepreneurship learning strategies that align with the characteristics of Generation Z within the framework of the Merdeka Curriculum. The findings are expected to serve as a foundation for developing educational programs that foster a resilient, creative, and independent young entrepreneurial generation.